30 Years of soft interventions to reduce car use – A systematic review and meta-analysis. (August 2020) - Semenescu, Alin; Gavreliuc, Alin; Sârbescu, Paul
Highlights: Soft transport interventions are effective measures for reducing personal car use. Effectiveness of soft interventions does not significantly decrease over time. Effectiveness was moderated by psychological variable targeted. Abstract: Soft travel interventions are generally regarded as effective measures for reducing personal car use. However, doubts about the validity of such claims are raised, primarily fueled by the low methodological quality of evaluation studies upon which such conclusions are based and by the fact that the literature is, for the most part, narratively synthesized. The present systematic review addresses these critiques by investigating the effect of soft interventions on car use through a meta-analysis, which includes only experimental and well-controlled quasi-experimental studies. Results revealed that interventions ( k  = 41) lead to a significant reduction of 7% in car modal split share (Hedges' g  = 0.163). Moderators of interventions' effectiveness were investigated in a meta-regression. Effectiveness was moderated by the type of intervention and by the main psychological variable targeted by the interventions, whereas the other studied moderators (i.e. residential relocation of participants, study design, percentage of females in the study, the presence of incentives, passed time to follow-up, interventions' measurement instrument, city size in which interventions were applied and the setting where they were conducted) were non-significant. Limitations of the present findings, together with implications for policy and practice are discussed.